Legal Nature of Bitcoin in Chilean Legal System (Justicia &Derecho, 2025)
The purpose of this paper is to analyze the legal nature of the cryptocurrency Bitcoin in the Chilean legal system. For this purpose, an approach to the figure of cryptoassets is made, to then describe the main characteristics of bitcoin. Subsequently, a dogmatic and normative analysis of both the specialized literature and the current legislation applicable to the matter is carried out. Considering the particular characteristics of bitcoin, as well as what is expressed by national and comparative doctrine, and especially, the terms of our Civil Code and 21.521 act “Fintec Act”, it is possible to sustain the impossibility of identifying bitcoin with any category of lege lata that allows to explain integrally the figure, being appropriate its qualification of sui generis asset according to national legal system.
Keywords: assets; blockchain; Civil Code; cryptocurrencies; Fintec Act